Analysis of Customer Value, Customer Satisfaction and Service Quality on Repurchase Intention with Customer Trust as Intervening Variables - Zaeni ZM, Ahmad (Publikasi Indonesia, 2022)
This study was conducted to determine the effect of customer value, customer satisfaction and service quality on money purchase intention with customer trust as an intervention variable. This research uses descriptive methods is a type of quantitative research with survey research. Data collection using research instruments, data analysis is quantitative or statistical. The population in this study are all individual users of electric railroad transportation (KRL) in Jabodetabek which reaches 154,591 (in thousands) passengers per year. In this study, the sample is several people among all KCI electric rail transportation customers in Jabodetabek who have made transactions. The analysis method used is the Structural Equation Model (SEM) to analyze the sample. The results of the research that have been described previously regarding the influence of Customer Value, Customer Satisfaction, Service Quality on Customer Trust and its impact on Repurchase Interest (Study on PT. KCI transportation service users during the Covid-19 pandemic) can be concluded as follows: 1) Customer Value, Customer Satisfaction, Service Quality, has a positive and significant effect on Customer Trust. That is, the better the customer value, the more satisfied the customer, the better the service it will increase customer trust.